Analysis of Financial Performance in Chemical Sector Industrial Companies Listed on the Indonesian Stock Exchange - Arsal, Muryani; Aisyah, Siti; Jusriani, Jusriani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2024)
This study aims to find out the conditions and financial performance of chemical industry companies listed on the Indonesian stock exchange in 2019-2022. The type of research used is quantitative research with a descriptive approach. This type of data uses secondary data obtained from financial reports. The sample in this company is 4 companies taken based on certain criteria with purposive sampling technique. The research results from the liquidity ratio as measured using the current ratio indicate that the chemical industry companies are categorized as in good condition, because the resulting value is already above the industry standard. The Solvency Ratio when measured using the debt to asset ratio is categorized in unfavorable condition because the resulting value is above the industry standard, the Activity Ratio which is measured using total asset turnover shows that chemical industry companies can be categorized in unfavorable condition because it is still below industry standard Profitability ratios as measured using return on equity indicate that chemical industry companies can be categorized as in unfavorable condition because the resulting value is still below the industry standard. It is expected that companies that have poor financial performance should re-evaluate their financial performance and increase revenue so that these companies can be even better and produce good financial performance.